2020
DOI: 10.3389/fimmu.2020.01361
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Cecropin-LL37 Hybrid Peptide Protects Mice Against EHEC Infection-Mediated Changes in Gut Microbiota, Intestinal Inflammation, and Impairment of Mucosal Barrier Functions

Abstract: Intestinal inflammation can cause impaired epithelial barrier function and disrupt immune homeostasis, which increases the risks of developing many highly fatal diseases. Enterohemorrhagic Escherichia coli (EHEC) O157:H7 causes intestinal infections worldwide and is a major pathogen that induces intestinal inflammation. Various antibacterial peptides have been described as having the potential to suppress and treat pathogen-induced intestinal inflammation. Cecropin A (1-8)-LL37 (17-30) (C-L), a novel hybrid pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 64 publications
2
22
0
Order By: Relevance
“…The results in accordance with expectation was that the restraint of well-recognized pathogenic bacteria Terrisporobacter [42], Lachnoclostridium [43,44], Clostridium_sensu_stricto_1 [33,45], Clostridium_sensu_stricto_6 [46] and unknown functional bacteria norank_f__Oscillospiraceae, unclassi ed_f__Prevotellaceae, etc. were notably observed after short-term lincomycin treated.…”
Section: Discussionsupporting
confidence: 87%
“…The results in accordance with expectation was that the restraint of well-recognized pathogenic bacteria Terrisporobacter [42], Lachnoclostridium [43,44], Clostridium_sensu_stricto_1 [33,45], Clostridium_sensu_stricto_6 [46] and unknown functional bacteria norank_f__Oscillospiraceae, unclassi ed_f__Prevotellaceae, etc. were notably observed after short-term lincomycin treated.…”
Section: Discussionsupporting
confidence: 87%
“…Intestinal microorganisms form a symbiotic ecosystem, which helps maintain the steady balance in intestine and is essential to the health of humans and animals ( 14 , 55 ). It is reported that intestinal inflammation will lead to changes in intestinal microorganisms, thus affecting the normal function of organisms ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…The immunomodulatory activity of AMPs mostly depends on its influence on the function of innate immune cells and mediators ( 12 ). In addition, AMPs (such as lactoferrin, polypeptide S100, LL-37, cecropin A) have the advantages of broad-spectrum antibacterial activity, small bioconcentration, and less possibility to cause bacterial resistance ( 13 , 14 ). Therefore, the researches on immune enhancement of AMPs have also become a hotspot in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, enterohemorrhagic Escherichia coli (EHEC) O157, a critical foodborne pathogen, infection is a major enteric pathogenic disease and primary cause of food contamination, diarrhea and death in humans, neonates and weaned animals. In addition, food spoilage caused by pathogenic microorganisms is also a cause of foodborne illness, which raises significant health concerns [5][6][7][8]. Antibiotic therapy has been used to control intestinal diseases for many years, but antibiotic resistance has rapidly emerged worldwide [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%